MMP-2,MMP-9andTIMP-2gene polymorphisms in Chinese patients with generalized aggressive periodontitis - Dong Chen (Blackwell Synergy, 2007)
Background: Aggressive periodontitis (AgP) has a genetic basis. It has been reported that the functional gene polymorphisms of matrix metalloproteinase (MMP)-2, MMP- 9 and tissue inhibitor of metalloproteinase-2 (TIMP-2) alter their expressions in transcriptional level and they are involved in the tissue destruction of periodontitis. The study was carried out to analyse the association of functional polymorphisms in MMP-2, MMP-9 and TIMP-2 with generalized AgP (G-AgP) in a Chinese population. Material and Methods: The study population consisted of 79 Chinese patients with G-AgP and 128 healthy controls. DNA was obtained from oral mucosa swab samples. MMP-2 genotypes were determined by PCR-based denaturing high-performance liquid chromatography analysis while MMP-9 and TIMP-2 genotypes were identified by a PCR-based restriction fragment length polymorphism. w2 test after Yates’ correction was used to investigate the possible association of the genotypes with the G-AgP. Results: Although gene polymorphisms for MMP-2 and MMP-9 did not show any association with the G-AgP, the analysis of the TIMP-2 418G to C gene polymorphism revealed significant differences between the patients and controls. Compared with controls, a significant increasing trend of TIMP-2 418C carrier in the G-AgP patients occurred (p50.013). Conclusion: It is suggested that the TIMP2 418G to C gene polymorphism is associated with G-AgP in the Chinese subjects.